PERAMALAN INDEKS HARGA PROPERTI RESIDENSIAL MENGGUNAKAN METODE BAYES - WIRYADANA, PUTU GDE BUDHA; SUMARJAYA, I WAYAN; SUKARSA, I KOMANG GDE (E-Jurnal Matematika; Vol 10 No 2 (2021)DO - 10.24843/MTK.2021.v10.i02.p324, 2021)
Residential property is a property in the form of building which serves as residence or house. House has function as a place whether to take a rest, to take cover and to get together with family. Residential property price indices (RPPIs) forecasting has aim as a development planning by the developer to avoid shortages or excess of home supplies. This research aims to model and predict the RPPIs using the Bayes method for 2020 to 2021. The data used in this research is the data from RPPIs of Denpasar city from 2012 in the first quarter to 2019 in the fourth quarter. Then, the method which is used is Bayes method with autoregression (AR) model in forecasting RPPIs. Therefore, it obtained mean absolute percentage error (MAPE) for forecasting the next one period with ( ) equal to 0,4049416%. For the result of RPPIs forecasting in Denpasar city from 2020 the first quarter to 2021 the fourth quarter has an insignificant increase with an average difference for each quarter increased by 0,3568%.